2022
DOI: 10.3390/w14192996
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Multi-Scale Meteorological Drought Characteristics over the Yangtze River Basin Based on CMIP6

Abstract: Drought is a common and greatly influential natural disaster, yet its reliable estimation and prediction remain a challenge. The object of this paper is to investigate the spatiotemporal evolution of drought in the Yangtze River basin. The multi-time scale drought characteristics were analyzed based on 19 models and 3 emission scenarios of CMIP6. The results show that the CMIP6 model generally has moisture deviation in the Yangtze River basin, but the accuracy has been improved after correction and ensemble. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…They found that the precipitation, soil moisture and runoff would increase, while more extreme and exceptional drought events were projected to occur in the future. Yu et al (2022) analysed the evolution of meteorological drought identified by SPI at multiple time scales in the YZB based on projections from 19 CMIP6 models and found that the YZB would become wetter but the variability would increase in the future, resulting in more severe drought events. Wang et al (2020) also found that the meteorological drought frequency and severity identified by SPEI would increase under 1.5 and 2°C warming scenarios.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…They found that the precipitation, soil moisture and runoff would increase, while more extreme and exceptional drought events were projected to occur in the future. Yu et al (2022) analysed the evolution of meteorological drought identified by SPI at multiple time scales in the YZB based on projections from 19 CMIP6 models and found that the YZB would become wetter but the variability would increase in the future, resulting in more severe drought events. Wang et al (2020) also found that the meteorological drought frequency and severity identified by SPEI would increase under 1.5 and 2°C warming scenarios.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The middle and lower reaches of the Yangtze River will face severe drought risks in the future, especially from 2030 to 2040 [50]. As the time scale increases, the number of drought events in the YRB first increases and then decreases, increasing the average duration and intensity [51]. Generally, the number of monthly scale events is the lowest, the number of seasonal scale events is the highest, and the harm of annual scale events is the greatest.…”
Section: Discussionmentioning
confidence: 99%
“…This basin is situated within a humid and semi-humid region with a remarkable monsoon climate. This implies that its response to climate change is intricate and volatile, as reflected in drought events with short-term fluctuations [44]. Consequently, it is susceptible to recurring seasonal drought events [45].…”
Section: Study Area and Datamentioning
confidence: 99%